2015
DOI: 10.1021/acs.cgd.5b00813
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphological Influences on Neptunium Incorporation in Uranyl Molybdates

Abstract: The in situ incorporation of pentavalent neptunium has been studied in the structurally related uranyl molybdate frameworks (NH 4 ) 4 [(UO 2 ) 5 (MoO 4 ) 7 ](H 2 O) 5 and (NH 4 ) 2 [(UO 2 ) 6 (MoO 4 ) 7 ](H 2 O) 2 prepared under similar synthetic conditions. The presence of Np(V) was confirmed by UV-vis-NIR spectroscopy in the first compound whereas Np(VI) was identified in the second based on the observation of a unit cell contraction and the lack of a spectral signature for Np(V). The incorporation of neptun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…It was also found that Np can be incorporated into the mineral structure by cation exchange or by substitution of a U VI for a Np V or Np VI ion in the mineral framework, with or without a compensating charge-balancing cation substitution . Within the available experimental data, it seems that the structure and/or chemical composition of the U mineral phase is of direct importance to the amount of incorporated Np . In this sense, several laboratory studies have already illustrated that the U alteration products can effectively retain Np by sorption or incorporation processes but then subsequently release it into the aqueous solution …”
Section: Introductionmentioning
confidence: 99%
“…It was also found that Np can be incorporated into the mineral structure by cation exchange or by substitution of a U VI for a Np V or Np VI ion in the mineral framework, with or without a compensating charge-balancing cation substitution . Within the available experimental data, it seems that the structure and/or chemical composition of the U mineral phase is of direct importance to the amount of incorporated Np . In this sense, several laboratory studies have already illustrated that the U alteration products can effectively retain Np by sorption or incorporation processes but then subsequently release it into the aqueous solution …”
Section: Introductionmentioning
confidence: 99%